PERSIAPAN PESERTA UJIAN MENGHADAPI UJI KOMPETENSI NASIONAL DIII KEBIDANAN - Rahmah Fitria (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
ABSTRACT The objective of this study was to look at the phenomenon of participant’s efforts in preparation for the National Diploma III Midwifery National competency test. The National Competency Test is an effort to measure the final result in the form of an outcome as a standard for measuring the knowledge, skills, and behavior of students in health institutions. This research used a qualitative design with a phenomenological approach. Data collection using the Snowball Sampling technique and collected using in-depth interviews conducted in a semi-structure. Data analysis refers to the constant comparative method and reliability is believed using triangulation. The results of the study revealed that all parties agreed with the policy of holding a national competency test but the participants opposed being carried out as an exit exam. The preparation that the exam participants did to face the Diploma III Midwifery National competency test used 3 methods, they were the private institution tutoring program, Self Directed Learning, and Institutional Guidance. Keywords: National Competency Test; Midwife Competency Test; Midwifery Diploma; Exam Preparation. ABSTRAK Penelitian bertujuan melihat fenomena upaya persiapan peserta mempersiapkan diri menghadapi uji kompetensi nasional DIII Kebidanan. Uji Kompetensi Nasional adalah suatu upaya pengukuran hasil akhir berupa outcome sebagai standar untuk mengukur pengetahuan, keterampilan dan perilaku peserta didik pada institusi bidang kesehatan. Desain penelitian adalah kualitatif dengan pendekatan fenomenologi. Pengumpulan data menggunakan teknik Snowball Sampling dan dikumpulkan dengan cara wawancara mendalam yang dilakukan secara semistruktur (Semistructure Interview). Analisis data mengacu pada constant comparative method dan kreabilitas diyakini dengan cara triangulasi. Hasil penelitian mengungkapkan bahwa semua pihak setuju dengan kebijakan diadakan uji kompetensi nasional tetapi peserta ujian menentang dilaksanakan sebagai exit exam. Persiapan yang peserta ujian lakukan untuk menghadapi uji kompetensi nasional DIII Kebidanan menggunakan Tiga metode yaitu mengikuti program lembaga swasta bimbingan belajar, Self Directed Learning dan Bimbingan Institusi. Kata kunci: Uji Kompetensi Nasional, Ukom Bidan, DIII Kebidanan, Persiapan Peserta Ujian.